JUDICIAL ANALYSIS OF PROVIDING LEGAL ASSISTANCE TO THE POOR IN REALIZING ACCESS TO JUSTICE - Zulfa Majida, Andi; Sururi; Itmam Aulia Rakhman (Jurnal Hukum Samudra Keadilan, 2024)
This study focuses on the implementation of free legal services for individuals by the Legal Aid Office (LBS) and the Ministry of Justice, in accordance with Law No. 16 of 2011 on Legal Aid. According to Article 1 paragraph 3 of the Law, the Legal Aid Office is a legal entity or a community organization that provides legal services. The aim of this study is to understand the function and role of the Human Rights Commission as law enforcement officers and to comprehend issues related to the implementation of legal services. The research method employed in this study is normative legal research, utilizing primary and secondary legal sources. Material analysis in this research involves committee work that systematically categorizes legal materials to facilitate the analysis of the research work. The study reveals that the primary authority for legal services lies with LBS/Orkemas, which is authorized to verify and accredit the Human Rights Commission as a legal service provider. Furthermore, the study emphasizes the importance of understanding the function and role of the Human Rights Commission as law enforcement officers and underscores their crucial involvement in the implementation of legal services. The research also highlights that the main authority for legal services is vested in LBS/Orkemas, which has been verified and accredited by the Human Rights Commission as a legal service provider.